2005
DOI: 10.1001/archderm.141.11.1373
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short-Contact Topical Tretinoin Therapy for Foot Ulcers in Patients With Diabetes

Abstract: Interventions: Patients were randomized to 4 weeks of daily treatment with either topical 0.05% tretinoin solution (Retin-A) or placebo saline solution. Photographs and assessment of wound size and appearance were assessed every 2 weeks for a total of 16 weeks. Main Outcome Measures:The proportion of ulcers that healed in each group and the degree of change in ulcer size.Results: Twenty-two patients, with a total of 24 foot ulcers, completed the study. At the end of 16 weeks, 2 (18%) of 11 ulcers in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…A similar randomized controlled trial with “short‐contact” topical tretinoin by Tom et al for patients with diabetic foot ulcers showed significantly decreased ulcer area and depth compared with placebo treatment over the 16‐week study period. This study was completed by 22 patients …”
Section: Evidence For Use Of Vitamin a On Chronic Woundsmentioning
confidence: 99%
“…A similar randomized controlled trial with “short‐contact” topical tretinoin by Tom et al for patients with diabetic foot ulcers showed significantly decreased ulcer area and depth compared with placebo treatment over the 16‐week study period. This study was completed by 22 patients …”
Section: Evidence For Use Of Vitamin a On Chronic Woundsmentioning
confidence: 99%
“…37,38 The current therapies for chronic wounds include a new generation of dressings (impregnated gauzes, films, hydrogels and hydrocolloids, alginates, foams), topical negative pressure, 39 or bioengineered skin substitutes (Integra, Alloderm, Biobrane, TranCyte, Oasis, Orcel, Epicel, Dermagraft, and Apligraft 37,40 ). Other adjuvant treatments are hyperbaric oxygen therapy, 41 tretinoin cream, 42 and the oral administration of pentoxifylline. 43 Many solutions have been developed in the last 20 years, but none can be applied to every chronic wound and often only surgery is the resolution.…”
Section: Nonhealing Wound Pathogenesismentioning
confidence: 99%
“…Paquette et al [11] have reported that shortcontact daily application of tretinoin topically improved the healing in five chronic leg ulcers. Tom et al [12] also investigated the efficacy and safety of short-contact topical tretinoin in a randomised control study of 24 patients with diabetic foot ulcers and concluded that short-contact topical tretinoin reduced both the surface area and depth of the ulcers.…”
Section: Introductionmentioning
confidence: 99%